DİNDARLIK, SİBER ZORBALIK VE PROBLEMLİ İNTERNET KULLANIMI İLİŞKİSİNE DAİR NİCEL BİR ARAŞTIRMA - MEHMEDOĞLU, ALİ ULVİ (My University, 2018)
Bu araştırmada, siber zorbalık/mağduriyet, problemli internet kullanımıve dindarlıkla ilişkili alanyazın incelenmiş ardından cinsiyet ve yaşa göre grupfarklılıkları ve değişkenlerin birbirleri arasındaki korelasyon ilişkileri ortayakonulmaya çalışılmıştır. Araştırma, 16-55 yaş arasındaki 1130 kişiden oluşankatılımcılardan elde edilen veriler üzerine yapılmıştır. Çalışmada Kişisel BilgiFormu, Yenilenmiş Siber Zorbalık Envanteri, Genellenmiş Problemli İnternetKullanımı-2 Ölçeği ve iki farklı Dindarlık Ölçeği kullanılmıştır. Araştırma-nın sonuçlarına göre cinsiyet ve yaşa göre siber zorbalık, problemli internetkullanımı ve dindarlıkta gruplar arasında istatistiki olarak anlamlı düzeydefarklılaşma olduğu görülmüştür. Dindarlık ile siber zorbalık/mağduriyet veproblemli internet kullanımı arasında negatif yönde anlamlı ilişkiler bulun-muştur.

In this research, firstly, the related literature of cyberbullying/victimization, problematic internet usage and religiosity and correlations among religiosity, cyberbullying/victimization and problematic internet use were tried to be revealed. Subsequently, the differences between the gender groups on cyberbullying/victimization, problematic internet use and religiosity were examined. Moreover, the differences among the age groups on cyberbullying/ victimization, problematic internet use and religiosity were analyzed. The study was conducted with 1130 participants between 16-55 years old. In the study, Personal Information Form, Revised CyberBullying Inventory, Generalized Problematic Internet Use Scale 2 (GPIUS2) and two different Religiosity Scales were utilized. Personal Information Form was arranged by researchers. Two items of the Personal Information Form are derived from the Bapint Scale who developed by Öğel and et al. Revised CyberBullying Inventory was developed by Topçu and Erdur-Baker. Generalized Problematic Internet Use Scale 2 (GPIUS2) was developed by Caplan in 2010. The first religiosity scale was developed by Veysel and this version edited by Ayten was used. The second religiosity scale was developed by Ayten. According to the results of the study, it was seen that there was a statistically significant difference in the cyber bullying variable according to the sex. However, according to sex, cyber victimization, problematic internet use and religiosity variables were found not to be significantly differentiated. There is a significant difference in the cyberbullying, problematic internet use and religiosity according to the age variable. It has been found that there is no significant difference in the cyber victimization variable. According to the correlation which have been obtained, the significant negative relationship between religiosity, cyber bullying/victimization and problematic internet use were found. It is possible to say that as the religiousness increases, cyberbullying, cyber victimization and problematic internet usage decrease.
A Quantitative Study on the Relationship Among Religiosity, Cyberbullying, and Problematic Internet Use
Keywords: Biyoloji; İletişim